Critical assessment of option pricing methods using Artificial Neural Networks - Andreou, Panayiotis; Charalambous, Chris; Martzoukos, Spiros H. (My University, 2002)
In this paper we compare the predictive ability of the Black-Scholes Formula (BSF) and Artificial Neural Networks (ANNs) to price call options by exploiting historical volatility measures. We use daily data for the S&P 500 European call options and the underlying asset and furthermore, we employ nonlinearly interpolated risk-free interest rate from the Federal Reserve board for the period 1998 to 2000.Using the best models in each sub-period tested, our preliminary results demonstrate that by using historical measures of volatility, ANNs outperform the BSF.In addition, the ANNs performance improves even more when a hybrid ANN model is utilized. Our results are significant and differ from previous literature. Finally, we are currently extending the research in order to: a) incorporate appropriate implied volatility per contract with the BSF and ANNs and b) investigate the applicability of the models using trading strategies.
Keywords: Economics; Neural networks; Electronic trading; Black-Scholes formula; Trading strategies; Federal Reserve; Risk assessment; Financial markets